Effect of antioxidants and packaging in controlling rancidity of banana chips during storage - Adrika B V (Department of Processing Technology, College of Agriculture, 2011)
The research project entitled “Effect of antioxidants and packaging in controlling rancidity of banana chips during storage” was conducted at Department of Processing Technology, College of Agriculture, Vellayani, with the objective to evaluate and compare the effect of antioxidants and packaging materials on the rancidity problem of banana chips, to delay the onset of oxidation during storage and to enhance shelf life of packed product. The whole experiment was divided into three parts viz., Standardization of frying parameters for banana chips preparation, Effect of antioxidants on quality of banana chips and Storage stability and acceptability of antioxidant treated banana chips. Frying two mm thick banana slices in unrefined coconut oil at 165oC, with an oil: slice ratio of 2:1 by adding 0.7 % salt and 0.15 % turmeric resulted in banana chips of higher acceptability. Two concentrations (0.01 and 0.02 %) of three different antioxidants viz., sodium ascorbate, tocopherol acetate and curry leaf powder were incorporated into banana chips in two different methods. Banana slices were either presoaked in antioxidants for 30 minutes or added directly to the frying oil. Addition of curry leaf in oven dried (at 600 C for 6 hours) and ground form was identified as the best method and form of curry leaf application for delaying the onset of rancidity. Experiment was laid out in CRD with two replications. The prepared chips were packed in trilayered laminated pouch (LDPE/metalized polyester /LDPE) and LDPE pouch for evaluation of shelf stability. Physical parameters like oil uptake and moisture content were lower for antioxidant treated chips, compared to untreated chips, indicating its superiority. Textural parameters like crispness and toughness were not affected by incorporating antioxidants in chips. Addition of group I antioxidants produced chips with lower moisture and oil uptake. These chips recorded a lower free fatty acid value and peroxide value compared to chips produced with group II and III indicating the inefficiency in combining the antioxidants. Chips prepared after adding antioxidants in oil had better physical and chemical quality parameters compared to the chips prepared from presoaked slices. Chips prepared after direct application of 0.02% curry leaf powder in oil showed superior physical and chemical parameters. These chips recorded higher organoleptic scores for texture, taste and overall acceptability. Their performance was better through out storage, hence can be considered as the best antioxidant tried for controlling rancidity of banana chips during storage also. There was an increase in moisture content, free fatty acid value and peroxide value and decrease in iodine value of chips during storage. Quality degradation was slower in laminated pouches compared to chips stored in LDPE. Banana chips produced after direct addition of 0.02 % curry leaf powder in oil had better physical, chemical and sensory characters, which are retained in storage when packed in laminated pouches.